Pentas Seni Sebagai Media Peningkatan Kepercayaan Diri Peserta Didik SMP Negeri 2 Taniwel Timur - Juliaans E. R. Marantika; Jolanda Tomasouw; Ronald Darlly Hukubun; Dewi Alma Tualepe; Preity Alfianty Sabina Fajri; Tridita Handayani; Amabelle Kenaya Evangelista Lona; Oldi Boy Belatu (Fakultas Teknik Universitas Cenderawasih, 2026)
This community service activity aims to boost the self-confidence of seventh-grade students at SMP Negeri 2 Taniwel Timur, West Seram Regency, many of whom struggle with speaking in public. The activity was conducted through an arts performance as part of the University of Pattimura’s Community Service Program (KKN). The process was divided into three simple stages: preparation (meetings with the school and selecting competitions such as public speaking, poetry reading, or solo singing), implementation (students performed for 2 hours while receiving praise and positive feedback), and evaluation (observing changes such as more confident eye contact and a louder voice). As a result, the students participated actively, and their hesitation decreased significantly due to hands-on practice and support from teachers and peers. The arts performance proved to be an easy and comprehensive way to help students become more confident and sociable.